A framework for evaluating societal safety interventions. (October 2021) - Hassel, Henrik; Cedergren, Alexander
Highlights: Evaluations of societal safety interventions are rare both in academia and practice. Complexity is an argument to be humble, not to avoid scrutinizing interventions. Lack of empirical feedback require alternative ways to approach evaluation. Systematic evaluations can form the basis for cross-organization learning. Abstract: Societal safety concerns maintaining critical social functions to protect the life and health of citizens as well as to meet their basic needs in times of crisis. Societal safety interventions are implemented by a range of actors in society. However, systematic evaluations of the suitability and effectiveness of proactive societal safety interventions are rather scarce – especially for complex interventions where impacts are difficult to directly observe or where there are delays between intervention and their effects. This may lead to interventions being implemented without support that they will actually improve societal safety. Some interventions may in fact be ineffective or even counter-productive. Another consequence of scarce evaluations may be that efforts to improve societal safety receive undue attention in organizations and in society since decision makers often need concrete arguments for the benefits of interventions in order to implement them. The present paper addresses this by proposing a framework aiming to guide the design of evaluation of societal safety interventions. The framework is based on previous research in areas such as evaluation and intervention research as well as risk and safety science and includes four main phases: 1. Frame the evaluation, 2. Develop a program theory, 3. Plan for data collection, analysis and feedback, 4. Reflect critically and continuously. With the proposed framework, we hope to contribute to increased use of in-depth evaluation of proactive societal safety interventions, which in turn can become an argument to spend resources on effective proactive measures – potentially both increasing societal safety and cost-efficiency of interventions. Increased use of evaluation in societal safety may be beneficial not only for the organization carrying out the evaluation but could also be a learning opportunity for other organizations intending to implement similar interventions.